Pengaruh Penyuluhan Menggunakan Media Video dengan Phantom Gigi terhadap Tingkat Pengetahuan Kesehatan Gigi dan Mulut pada Anak - Ni Luh Putu Deswita; Mahardika, I Made Rai; Diwyami, Ni Putu (ProHealth Journal, 2025)
School-age children are a vulnerable group regarding dental and oral health because during this period children begin to develop habits of maintaining healthy teeth and mouth that will last until adulthood. A person's habits are determined by the level of knowledge they have, one way to increase a person's knowledge is through health education. This research aimed to understand the comparison of the effect of counseling using video media with dental phantoms on the level of dental and oral health knowledge of grade V children at elementary school pembina negeri tulang ampiang. Methods : Quasi- experimental study using a two group pretest-posttest design approach. The sample used was 80 respondents divided into 2 groups using the lottery method. Data collection uses questionnaires. Result there is a significant difference in the average level of dental and oral health knowledge before and after being given health education using dental phantom media, with a value of p = 0.00. There is a significant difference in the average level of dental and oral health knowledge before and after being given health education using video media with a value of p = 0.00. There is a significant difference in mean comparison between counseling using dental phantom media and video media with a value of p = 0.038. Conclucion : counseling using dental phantom media is more effective than counseling using video media.